Peran Museum Benteng Vredeburg dalam Upaya Edukasi Masyarakat Yogyakarta - Dwi Rahyu Amalianti (Forum for Social and Humanities Studies, 2026)
Museums play a central role in maintaining, preserving, and disseminating the nation's historical heritage to the public. Yogyakarta's Vredeburg Fortress Museum is a historic museum that has made a significant contribution to the publication of national struggle values ​​and national character education. This study aims to analyze how the Vredeburg Fortress Museum carries out its historical publication function through educational activities, collection management, public communication strategies, and the use of digital technology. The research method used is qualitative with a phenomenological approach. Data were obtained from previous research, museum activity reports, archival documents, and secondary sources relevant to the themes of history learning and modern museum management. The results show that the Vredeburg Fortress Museum not only functions as a place to preserve historical artifacts, but has also transformed into an interactive public education center. Through thematic exhibition programs, virtual tours, field education activities, and the development of digital media, the museum has expanded access to historical information for the wider community, especially the younger generation. The implementation of digital-based and educational communication strategies makes the museum more inclusive, engaging, and relevant to current developments. In addition, the museum also plays a strategic role in shaping historical awareness, strengthening national identity, and fostering appreciation for Indonesia's struggle for independence. In conclusion, the Vredeburg Fortress Museum plays a significant role as a dynamic, participatory, and technologically adaptive historical learning medium. Innovations in historical publications have increased public interest and strengthened the museum's role as a space for learning and preserving national values ​​in the digital age.